Technical and tactical evolution of the offensive team sequences in LaLiga between 2008 and 2021. Is Spanish football now a more associative game? - González-Rodenas, J.; Moreno-Pérez, V.; López-Del Campo, R.; Resta, R.; Del Coso, J. (Biology of Sport, 2024)
The aim of this investigation was to study the technical and tactical evolution of the offensive team sequences in the Spanish football teams from 2008/09 to 2020/21. A comparative analysis including twelve variables related to the development of offensive sequences in 4940 matches was performed from 2008/09 to 2020/21 seasons of the Spanish professional football league (LaLiga). All match observations were recorded using a validated video tracking system. Multilevel linear mixed models were used to examine the differences across seasons, considering the effects of contextual variables. The number of passes per sequence (2.4 [CI: 2.2-2.5] vs 3.2 [CI: 3.0-3.4]; +33.3%), the passing accuracy (72.1 [CI: 70.6-73.5] vs 76.9 [CI: 75.4-78.3]%; +6.8%) and the average duration of the team sequences (6.4 [CI: 5.9 6.8] vs 8.3 [CI: 7.8-8.7] seconds; +25.76%) showed a small increasing trend over the seasons (P < 0.05). In contrast, variables such as the direct speed of progression (2.2 [CI: 2.1-2.3] vs 1.6 [CI: 1.5-1.7] metres/second; -24.5%), key passes (8.1 [CI: 7.6-8.5] vs 6.8 [CI: 6.3-7.2]; -15.8%), and the sequences that ended in the attacking third (64.8 [CI: 62,7-66.8] vs 57.1 [CI: 55.1-59.2]; -11.7%) or in a shot (13.0 [CI: 12.4-13.6] vs 10.2 [CI: 9.6-10.8]; -21.6%) showed a small decreasing trend from 2008/09 to 2020/21 (P < 0.05). Spanish professional football teams slightly evolved technically and tactically towards a more associative style of play that includes longer passing sequences. This evolution also involved a decreasing speed of progression and fewer technical actions such as through balls, key passes and shots.